HOME IN THE POETRY OF SAUDI ARABIA POETS: Taher Zamakhshari an Example of a Distinguished Arab - Dahami, Yahya Saleh Hasan (Islamijah: Journal of Islamic Social Sciences, 2025)
Poets always glorify and praise the homeland. The homeland is an absolutely crucial matter among Saudi poets, Arab poets, and, I can say, among every thoughtful human being. Several Saudi poets dealt with the same issue, presenting us with gorgeous lyrical poetic pieces praising their homeland, the Kingdom of Saudi Arabia. Through the poem "My Homeland (وطني)" by Taher Zamakhshari, the study intends to underline the poet's capability, awareness, and proficiency while similarly proving the poet’s sentiment and loyalty for the glorious homeland. It attempts to make a tangible effort to value, assess, and appraise the poet's faculty and aptitude through drawing on poetic metaphors, pictures, and symbols in his poem understudy. The analysis commences with a short introduction to poetry and its significance, followed by a glance at Saudi Poetry: The Beating Heart of All Genres of Literature, and then another glance at the career of the Saudi poet Taher Zamakhshari. The chief issue of the research is the critical-analytical-descriptive approach to the poem "My Homeland." The paper employs such a technique, paying great attention to the conception of homeland since it is the primary theme. The paper, after that, ends with a discussion and a conclusion.